A sala de aula UFQ: útil, funcional e de qualidade - uma intervenção prática para a melhoria das disciplinas teóricas - - Cardoso, Michele (2004)
This dissertation is the result of a case study developed in the Course of Drawing and Plastic of UFSM, and aims at proposing a practical intervention in classrooms for improvement in theoretical disciplines. The preliminary stage of the work consists in the listing and analysis of the appropriateness and conditions of use of the equipments and furniture in the rooms. Participant observation and questionnaires were employed to identify the students and teachers needs. A briefing of constraints and requirements was elaborated and a proposal was made taking into consideration the peculiarities of the course. The main contribution of piece of work is the layout for classrooms and the design of a product relative to the Course of Drawing and Plastic. The motivation for studying this theme is the need for demonstrating that the resources and knowledge available within the academic field can and should be used to make the desired changes and to solve a number of the problems we meet.